The effect of outer tube on quasi-static compression behavior of aluminum foam-filled tubes. (1st August 2020) - Yang, Xudong; An, Tao; Wu, Ziqing; Zou, Tianchun; Song, Haipeng; Sha, Junwei; He, Chunnian; Zhao, Naiqin
Highlights: Effect of strength of tubes on performance of aluminum foam-filled tubes. Crush behavior of aluminum foam-filled tubes at elevated temperatures. A new criterion to predict the deformation mode of aluminum foam-filled tubes. Abstract: In this paper, two types of the foam-filled tubes (FFTs), including O-FFTs and T6-FFTs, were prepared by directly inserting Al foams (AFs) into 6061-O Al alloy empty tubes (O-ETs) and 6061-T6 Al alloy empty tubes (T6-ETs), respectively. Quasi-static compression tests of studied specimens were carried out using an environmental chamber under the temperatures ranging from 25 °C to 250 °C. The results show that the mechanical properties of FFTs decrease with temperature increasing. The T6-FFTs show better energy absorption capacities while the deformation modes are less stable than the O-FFTs. The T6-ETs and T6-FFTs change the deformation mode when the temperature is higher than 150 °C. Both of the number of defects and the lengths of cracks decrease for the T6-FFTs with the increment of temperature. A couple of criteria are proposed to effectively describe and predict the deformation mode of FFTs under quasi-static compression.